Response of antioxidant metabolism to NaCl stress in the halophyte Salicornia brachiata Roxb. - S. Sridevi, A.Venkatesan (Journal of Phytology, 2009)
The present study was conducted to determine how salinity affects growth and enzymatic activity in shoot and root organs of Salicornia brachiata Roxb. The seedlings were treated with various concentration of exogenous addition of NaCl ranging from 0 to 700mM was added. The 700mM NaCl treatment significantly reduced the growth rate. The shoot and root length, fresh and dry weight increased significantly upto 400mM NaCl and thereafter drastically reduced. The antioxidant enzyme such as catalase (CAT), peroxidase (PO), polyphenoloxidase (PPO), superoxide dismutase (SOD) activity increased upto 400mM NaCl. Beyond this level all the enzyme activity gradually reduced. The increase in the enzyme activity was probably due to the direct influence of salt stress on enzyme synthesis and the induction of enzyme synthesis by salt stress may play a role in the salt tolerance.